Manajemen Kewirausahaan Sekolah Melalui Usaha Budidaya Lele dan Sayur Secara Aquaponik Berbasis Energi Baru Terbarukan Di Pulau Balang Lompo - Fadhilah, Nurul; Tahir, Rahmatia; Alamsyah, Aylee Cristine; Wa, Muhammad; Swandi, Ahmad; Rahim, Abdurrachman (Jurnal Pengabdian Kepada Masyarakat (MEDITEG), 2024)
This program aims to improve students' and teachers' practical skills in entrepreneurship management and educate them about the aquaponic system that integrates solar energy as an energy source. The implementation method follows 5 stages: socialization, training, technology application, mentoring and evaluation, and program sustainability. The core activities were carried out for 3 days at SMPN 1 Liukkang Tupabbiring, which included training on aquaponic vegetable and fish cultivation, using solar power as a source of electricity and managing student entrepreneurial products. The results of this program showed a significant increase in entrepreneurial knowledge and skills and students' understanding of solar-based aquaponic systems. In addition, this project also produced an aquaponic system with a capacity of 120 pots and 350 fish. The products of this PKM are also expected to be a model for other schools in implementing the concept of entrepreneurship and green technology, especially on Balang Lompo Island, as well as supporting environmental conservation efforts and sustainable development at the local level.